Rituximab Maintenance Versus Observation After Immunochemotherapy (R-CHOP, R-MCP, and R-FCM) in Untreated Follicular Lymphoma Patients: A Randomized Trial of the Ostdeutsche Studiengruppe Hämatologie und Onkologie and the German Low-Grade Lymphoma Study Group. Issue 7 (23rd July 2021) - Hirt, Carsten; Hoster, Eva; Unterhalt, Michael; Hänel, Mathias; Prange-Krex, Gabriele; Forstpointner, Roswitha; Florschütz, Axel; Graeven, Ullrich; Frickhofen, Norbert; Wulf, Gerald; Lengfelder, Eva; Lerchenmüller, Christian; et al.
Abstract : The German study groups, the German Low-Grade Lymphoma Study Group (GLSG) and Ostdeutsche Studiengruppe Hämatologie und Onkologie (OSHO), initiated in 2007 a double randomized trial to investigate efficacy and safety of rituximab maintenance versus observation in remission after randomly assigned induction treatment in the first-line follicular lymphoma. Previously untreated patients with stage II–IV follicular lymphoma in need of therapy were randomized to receive 6 cycles of R-CHOP, R-MCP, or R-FCM. Responding patients were subsequently randomized to 2 years rituximab maintenance or observation, stratified by type of immunochemotherapy, quality of remission, and Follicular Lymphoma International Prognostic Index (FLIPI). Recruitment was stopped in 2011 after the PRIMA results had been published. Median age of the 206 recruited patients was 66 years (range, 24–86), and (FLIPI) was low in 13%, intermediate in 28%, and high in 60%. High and comparable overall response rates were observed after R-CHOP (88%), R-MCP (89%), and R-FCM (91%). Rituximab maintenance substantially prolonged progression-free survival (PFS) in comparison to observation in remission (hazard ratio 0.39, P = 0.0064). In the rituximab maintenance group, the 3-year PFS was 89% compared with 69% in the observation group. No differences in overall survival were observed for maintenance vs. observation (hazard ratio 1.04, 95% confidence interval 0.32–3.43, P = 0.95). In this randomized trial, 2 years of rituximab maintenance was associated with significantly prolonged PFS in comparison to observation after response to first-line immunochemotherapy in follicular lymphoma. Our data represent an independent confirmation of the PRIMA trial results. (Clinical Trial EudraCT Number: 2005-005473-29, 2006-09-26)